The Effect of Model Availability, Prices, and Promotions on Consumer Purchasing Interest in Vans Shoe Products - Ayyanhar, M.; Djafar, A.; Gunawan, Hamzah (Research Horizon, 2024)
This study aims to investigate the impact of model availability, price, and promotion on consumer purchasing intention towards Vans footwear products among university students in Yogyakarta. The research employs a survey approach to collect data from respondents who are students from various universities in Yogyakarta. Regression analysis is utilized to evaluate the relationship between the independent variables (model availability, price, and promotion) and the dependent variable (consumer purchasing intention). The gathered data will be comprehensively analyzed to assess how model availability, offered prices, and promotional strategies influence consumer purchasing intention for Vans footwear products in the student market of Yogyakarta. Findings from this study are expected to contribute to enriching the literature on consumer behavior and marketing strategies in the fashion product sector, particularly within the context of the student segment.